2021
DOI: 10.31234/osf.io/jbtng
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How Pills Undermine Skills: Moralization of Cognitive Enhancement and Causal Selection

Abstract: Despite the promise to boost human potential and wellbeing, enhancement drugs face recurring ethical scrutiny. The present studies examined attitudes toward cognitive enhancement in order to learn more about these ethical concerns, who has them, and the circumstances in which they arise. Fairness-based concerns underlay opposition to competitive use—even though enhancement drugs were described as legal, accessible and affordable. Moral values also influenced how subsequent rewards were causally explained: Oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…All participants accepted the lowest ambitious objective: identification of ethical issues in practice. It was not viewed as an important objective mainly because empirical research was assumed to be hypothesis driven, in line with experimental strands of empirical bioethics [16,19,21]. Therefore, this objective was not considered a driving force of empirical research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants accepted the lowest ambitious objective: identification of ethical issues in practice. It was not viewed as an important objective mainly because empirical research was assumed to be hypothesis driven, in line with experimental strands of empirical bioethics [16,19,21]. Therefore, this objective was not considered a driving force of empirical research.…”
Section: Discussionmentioning
confidence: 99%
“…Because ethical arguments are entangled with empirical assumptions about stakeholders and conditions of reasoning, bioethics welcomes many potential objectives of empirical research that are relevant for moral questions. For instance, descriptive ethics studies explore stakeholders' responses to bioethical questions and try explain how people arrive at certain moral opinions and reasoning patterns [13][14][15][16][17][18][19][20][21][22]. Empirical research can investigate whether people and healthcare professionals comply with ethical guidelines and how ethical solutions are translated into practice [13-15, 18, 23-29].…”
Section: Introductionmentioning
confidence: 99%
“…Experiment 1 did not reveal an effect of access on moral approval. Relatedly, previous research on cognitive enhancement found that stipulating equal access to a neurostimulant did not suffice to neutralize laypeople's moral disapproval of enhancement in competitive contexts [17].…”
Section: Limitations and Future Directionsmentioning
confidence: 96%
“…As a result, access to enhancement will not be distributed uniformly throughout the target population-and it is the economically advantaged who disproportionately reap the benefit of enhancement technologies. This raises ethical concerns about unfairness [14][15][16][17][18][19] and social inequality [9,20] that undergird certain cautionary views in the enhancement debate.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, rather than relying on unrealistic, abstract thought experiments to identify the contours of what is morally at stake in some issue (e.g., Thomson's "violinist" analogy in arguments about abortion; for discussions, see Walsh 2011;McMillan 2018), bioxphi tends to deal with cases that are more directly inspired by real-world dilemmas and decisions. These might pertain, for example, to specific healthcare policy options or standards of clinical practice (Kingsbury and Hegarty 2022), to medical research and rules proposed to protect participants' rights (Dranseika et al unpublished), to the understanding, use, or application of relevant legal concepts (Sommers 2020;Demaree-Cotton and Sommers 2022), to evaluation and regulation of cognitive enhancement or other emerging biotechnologies (Faber et al 2016;Mihailov et al 2021b), or (more generally) to human-technology and human-biosphere relations (for overviews, see Earp 2019;Earp et al 2020aEarp et al , 2021Earp et al , 2022.…”
Section: Introductionmentioning
confidence: 99%